The study of maternal and foetal outcome in pregnant women with thyroid disorder - Maurya, Priya; Chaudhary, Neeta; Tyagi, Natasha; Kural, M. R.; Bhatnagar, Kriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Thyroid disorder is one of the most common disorder in pregnancy. Thyroid disorder is known to be associated with abnormal maternal and foetal outcomes and overlooked in pregnant women because of non-specific symptoms and hypermetabolic state of pregnancy of pregnancy. It is well established that not only overt, but subclinical thyroid dysfunction also has adverse effects on mother and the foetus like miscarriages, preterm delivery, pre-eclampsia, eclampsia, polyhydramnios, placental abruption, postpartum haemorrhage, low birth weight, neonatal hypothyroidism. Decreased availability of thyroid hormones may also impair neurological and intellectual development of foetus. With this background, we are conducting a study to know the effect of thyroid disorder on pregnancy and its maternal and foetal outcome. Methods: The present study was conducted in Muzaffarnagar Medical College, Uttar Pradesh, India in collaboration of department of Gynecology and Obstetrics and Pediatrics Department. It is a prospective random cross-sectional study done over 400 pregnant women which includes known cases of thyroid disorder. Serum thyroid stimulating hormone (TSH) test was apart from the routine blood sample investigations as per FOGSI-ICOG good clinical practice recommendation. fT3, fT4 and thyroid peroxidase antibody test were done in patients with a deranged TSH value. Patients were followed up till delivery, and their obstetrics and perinatal outcomes were noted and managed. Results: In present study out of 400 cases, 25 cases are hypothyroidism and 16 cases are hyperthyroidism in pregnancy. Out of these 41 patients with thyroid dysfunction, complications associated were abortions (14.63%), maternal anaemia (9.7%), pre-eclampsia (12.2%), preterm labour (9.76%), abruption placenta (4.88%), IUGR (2.4%), Still birth (7.32%). Out of 41 patients with thyroid dysfunction, foetal complications seen were hyperbilirubinemia (12.2%), Foetal distress (4.88%), NICU admission (17.07%) and low birth weight (21.95%). Conclusions: Thyroid disorder in pregnancy have adverse effects on maternal and foetal outcome emphasizing the importance of routine antenatal thyroid screening.